A De Novo Chromosome-Level Genome Assembly of the White-Tailed Deer, Odocoileus Virginianus. (3rd May 2022) - London, Evan W; Roca, Alfred L; Novakofski, Jan E; Mateus-Pinilla, Nohra E
Abstract: Cervids are distinguished by the shedding and regrowth of antlers. Furthermore, they provide insights into prion and other diseases. Genomic resources can facilitate studies of the genetic underpinnings of deer phenotypes, behavior, and disease resistance. Widely distributed in North America, the white-tailed deer ( Odocoileus virginianus ) has recreational, commercial, and food source value for many households. We present a genome generated using DNA from a single Illinois white-tailed sequenced on the PacBio Sequel II platform and assembled using Wtdbg2. Omni-C chromatin conformation capture sequencing was used to scaffold the genome contigs. The final assembly was 2.42 Gb, consisting of 508 scaffolds with a contig N50 of 21.7 Mb, a scaffold N50 of 52.4 Mb, and a BUSCO complete score of 93.1%. Thirty-six chromosome pseudomolecules comprised 93% of the entire sequenced genome length. A total of 20 651 predicted genes using the BRAKER pipeline were validated using InterProScan. Chromosome length assembly sequences were aligned to the genomes of related species to reveal corresponding chromosomes.